2011
DOI: 10.1007/s11420-011-9198-z
|View full text |Cite
|
Sign up to set email alerts
|

Iliopsoas Impingement: A Newly Identified Cause of Labral Pathology in the Hip

Abstract: Labral tears typically occur anterosuperiorly in association with femoroacetabular impingement or dysplasia. Less commonly, labral pathology may occur in an atypical direct anterior location adjacent to the iliopsoas tendon in the absence of bony abnormalities. We hypothesize that this pattern of injury is related to compression or traction on the anterior capsulo-labral complex by the iliopsoas tendon where it crosses the acetabular rim. In a retrospective review of prospectively collected data, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
215
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(223 citation statements)
references
References 41 publications
2
215
0
6
Order By: Relevance
“…Arthroscopic resection of an impinging AIIS has also been reported by some experienced hip arthroscopists [21,23,25,27], and studies have shown good short-term outcomes up to two years follow-up for a return to sporting activity, increased ROM, Harris hip score and visual analogue scale [21,23,27]. To date, post-surgical rehabilitation has not been objectively studied and its role in the post-operative period is poorly detailed in the literature [18], while two to four weeks of protected weight bearing with crutches and ROM exercises until basic muscle strength is regained are recommended [28]. The post-operative administration of non-steroidal antiinflammatory agents for prophylaxis against heterotopic ossification for the first three to four weeks after surgery is also advised [23].…”
Section: Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Arthroscopic resection of an impinging AIIS has also been reported by some experienced hip arthroscopists [21,23,25,27], and studies have shown good short-term outcomes up to two years follow-up for a return to sporting activity, increased ROM, Harris hip score and visual analogue scale [21,23,27]. To date, post-surgical rehabilitation has not been objectively studied and its role in the post-operative period is poorly detailed in the literature [18], while two to four weeks of protected weight bearing with crutches and ROM exercises until basic muscle strength is regained are recommended [28]. The post-operative administration of non-steroidal antiinflammatory agents for prophylaxis against heterotopic ossification for the first three to four weeks after surgery is also advised [23].…”
Section: Managementmentioning
confidence: 99%
“…In other words, iliopsoas impingement causes a distinct pattern of anterior labral damage that does not extend into the anterosuperior portion of the labrum (e.g., 1 to 2-o'clock position for right hips). It is an emerging diagnosis of anterior hip pain that has been linked to acetabular labral tears [28,35], and also to impingement on the osteophytic acetabular rim in a patient with degenerative hip arthritis [36].…”
Section: Iliopsoas Impingement Anatomical Considerationsmentioning
confidence: 99%
See 3 more Smart Citations